Desain Model Tata Kelola Layanan Informasi Menggunakan Customer Relationship Management - Saptadi, Tri Suswanto; Marwi, Hans Christian (TEMATIKA, Journal of Informatics and Information Systems, 2014)
Information services for stakeholders in a hospital need to be in good governance. The rapid development of IT has changed the ordinance of people in thinking, bearing, behaving and acting. Advances in technology that are growing exponentially can potentially result in a number of changes to the governance situation in a hospital environment. The research focuses on the modeling of information services function governance in an effort to create competitiveness to help improve the value of profitability and accountability. Based on analysis of the use of information technology, a description was obtained in blueprint draft about the addition of the functional services based on Customer Relationship Management. The method used is descriptive analysis and structured approach which are parts of the System Development Life Cycle (SDLC). Stages include survey and requirement analysis, as well as the design of model systems about business process based on a database system. The result is a research information services governance model.Keywords: Model, Governance, Service